2023
DOI: 10.3389/fphar.2023.1110922
|View full text |Cite
|
Sign up to set email alerts
|

Role of exosomes in hepatocellular carcinoma and the regulation of traditional Chinese medicine

Abstract: Hepatocellular carcinoma (HCC) usually occurs on the basis of chronic liver inflammatory diseases and cirrhosis. The liver microenvironment plays a vital role in the tumor initiation and progression. Exosomes, which are nanometer-sized membrane vesicles are secreted by a number of cell types. Exosomes carry multiple proteins, DNAs and various forms of RNA, and are mediators of cell-cell communication and regulate the tumor microenvironment. In the recent decade, many studies have demonstrated that exosomes are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 222 publications
0
7
0
Order By: Relevance
“…Exosomes have also been studied for their potential role in hepatic regeneration, including liver tissue repair and regrowth after injury or damage. The liver has a remarkable ability to regenerate, and exosomes have been shown to contribute to this process; they can stimulate the proliferation of hepatocytes, which are the primary functional cells of the liver and are crucial for tissue repair 110 , 111 . Exosomes can also enhance the migration of liver progenitor cells, which are involved in liver regeneration and differentiation.…”
Section: Applications Of Exosome-loaded Biomaterialsmentioning
confidence: 99%
“…Exosomes have also been studied for their potential role in hepatic regeneration, including liver tissue repair and regrowth after injury or damage. The liver has a remarkable ability to regenerate, and exosomes have been shown to contribute to this process; they can stimulate the proliferation of hepatocytes, which are the primary functional cells of the liver and are crucial for tissue repair 110 , 111 . Exosomes can also enhance the migration of liver progenitor cells, which are involved in liver regeneration and differentiation.…”
Section: Applications Of Exosome-loaded Biomaterialsmentioning
confidence: 99%
“…MiR-21 contributes to the acquired resistance to sorafenib by suppressing autophagy through the Akt/ PTEN pathway in HCC [20] . Furthermore, in 2019, Tian et al discovered that the acidic microenvironment in HCC induces the release of miR-21-enriched exosomes to promote cancer cell proliferation and metastasis [88] . Based on these findings, we hypothesize that the transmission of miR-21 through exosomes in response to an acidic microenvironment among HCC cells could suppress autophagy by modulating the Akt/PTEN pathway, which plays a crucial role in the acquisition of sorafenib resistance in HCC.…”
Section: Exosomes Induce Autophagy In Drug Resistancementioning
confidence: 99%
“…Liver cancer is one of the most common malignant tumours, and its prevalence and death rates have risen worldwide in recent years [ 1 ]. Statistics showed that 90% of liver cancers are hepatocellular carcinomas (HCCs) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Liver cancer is one of the most common malignant tumours, and its prevalence and death rates have risen worldwide in recent years [ 1 ]. Statistics showed that 90% of liver cancers are hepatocellular carcinomas (HCCs) [ 1 ]. Traditional therapies for HCC include surgery, chemotherapy, radiotherapy, targeted therapy, and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation